Measurements of dichroic bow-tie antenna arrays with integrated cold-electron bolometers using YBCO oscillators - Revin, Leonid S.; Pimanov, Dmitry A.; Chiginev, Alexander V.; Blagodatkin, Anton V.; Zbrozhek, Viktor O.; Samartsev, Andrey V.; Orlova, Anastasia N.; Masterov, Dmitry V.; Parafin, Alexey E.; Safonova, Victoria Yu.; Gordeeva, Anna V.; Pankratov, Andrey L.; et al. (Beilstein Journal of Nanotechnology, 2024)
We consider properties of dichroic antenna arrays on a silicon substrate with integrated cold-electron bolometers to detect radiation at frequencies of 210 and 240 GHz. This frequency range is widely used in cosmic microwave background experiments in space, balloon, and ground-based missions such as BICEP Array, LSPE, LiteBIRD, QUBIC, Simons Observatory, and AliCPT. As a direct radiation detector, we use cold-electron bolometers, which have high sensitivity and a wide operating frequency range, as well as immunity to spurious cosmic rays. Their other advantages are the compact size of the order of a few micrometers and the effect of direct electron cooling, which can improve sensitivity in typical closed-loop cycle 3He cryostats for space applications. We study a novel concept of cold-electron bolometers with two SIN tunnel junctions and one SN contact. The amplitude–frequency characteristics measured with YBCO Josephson Junction oscillators show narrow peaks at 205 GHz for the 210 GHz array and at 225 GHz for the 240 GHz array; the separation of these two frequency bands is clearly visible. The noise equivalent power level at an operating point in the current bias mode is 5 × 10−16 W/√Hz.
Keywords: cosmic microwave background; B mode; cold-electron bolometer; dichroic antenna array; dipole bow-tie antenna; Josephson junction; LSPE